POLA PENGELUARAN MAHASISWA FKIP INDEKOS UNIVERSITAS KLABAT - Grifin Zachary Roring; Andrew Christian Aseng; Lanemey Brigitha Pandeirot (Nusantara Hasana Berdikari, 2022)
This study aims to find out and describe the spending patterns of Universitas Klabat (UNKLAB) students who live in boarding houses (outsiders) around campus. The research instrument is a questionnaire that was distributed online using the convenience sampling method to students of the Fakultas Keguruan dan Ilmu Pendidikan UNKLAB who live in boarding houses. The data analysis technique used is descriptive analysis to explain how the students spending pattern for food and non-food categories are. The results showed that the overall food and non-food expenses of students living in boarding houses were not much different. Based on gender, female students spend more than male students and there are statistically significant differences in the variables of snacks, public transportation, cosmetics, and clothing.